Plasma ghrelin levels and hunger scores in humans initiating meals voluntarily without time- and food-related cues - Cummings, D. E; Frayo, R. Scott; Marmonier, Corinne; Aubert, Roberte; Chapelot, Didier (American journal of physiology: endocrinology and metabolism, 2004)
1 Division of Metabolism, Endocrinology, and Nutrition, Department of Medicine, University of Washington, Veterans Affairs Puget Sound Health Care System, Seattle, Washington 98108; 2 Laboratoire de Physiologie du Comportement Alimentaire, Unité de Formation et de Recherche Santé Médecine and Biologie Humaine, Université Paris 13, Bobigny 93014; and 3 Laboratoire de Nutrition Humaine, Faculté Xavier Bichat, Université Paris VII, Paris, 75018 France Submitted 22 December 2003 ; accepted in final form 9 March 2004 Ghrelin is an orexigenic hormone that is implicated in meal initiation, in part because circulating levels rise before meals. Because previous human studies have examined subjects fed on known schedules, the observed preprandial ghrelin increases could have been a secondary consequence of meal anticipation. A causal role for ghrelin in meal initiation would be better supported if preprandial increases occurred before spontaneously initiated meals not prompted by external cues. We measured plasma ghrelin levels among human subjects initiating meals voluntarily without cues related to time or food. Samples were drawn every 5 min between a scheduled lunch and a freely requested dinner, and hunger scores were obtained using visual analog scales. Insulin, glucose, fatty acids, leptin, and triglycerides were also measured. Ghrelin levels decreased shortly after the first meal in all subjects. A subsequent preprandial increase occurred over a wide range of intermeal intervals (IMI; 320425 min) in all but one subject. Hunger scores and ghrelin levels showed similar temporal profiles and similar relative differences in magnitude between lunch and dinner. One subject displayed no preprandial ghrelin increase and was also the only individual whose insulin levels did not return to baseline between meals. This finding, along with a correlation between area-under-the-curve values of ghrelin and insulin, suggests a role for insulin in ghrelin regulation. The preprandial increase of ghrelin levels that we observed among humans initiating meals voluntarily, without time- or food-related cues, and the overlap between these levels and hunger scores are consistent with a role for ghrelin in meal initiation. appetite; insulin Address for reprint requests and other correspondence: D. E. Cummings, Univ. of Washington, VA Puget Sound Health Care System, 1660 South Columbian Way, S-111-Endo, Seattle, WA 98108 (E-mail: davidecatu.washington.edu ).